Biochemical responses to ocean acidification contrast between tropical corals with high and low abundances at volcanic carbon dioxide seeps. (2nd November 2015) - Strahl, J.; Francis, D. S.; Doyle, J.; Humphrey, C.; Fabricius, K. E.
Abstract: At two natural volcanic seeps in Papua New Guinea, the partial pressure of carbon dioxide ( p CO2 ) in the seawater is consistent with projections for 2100. Here, the cover of massive scleractinian corals Porites spp. is twice as high at elevated compared with ambient p CO2, while that of branching corals such as Acropora millepora is greater than twofold reduced. To assess the underlying mechanisms for such community shifts under long-term exposure to elevated p CO2, biochemical parameters related to tissue biomass, energy storage, pigmentation, cell protection, and cell damage were compared between Porites spp. and A. millepora from control (mean pHtotal = 8.1, p CO2 = 323 µatm) and CO2 seep sites (mean pHtotal = 7.8, p CO2 = 803 µatm) each at two reefs. In Porites spp., only one of the biochemical parameters investigated (the ratio of photoprotective to light-harvesting pigments) responded to p CO2, while tissue biomass, total lipids, total proteins, and some pigments differed between the two reefs, possibly reflecting differences in food availability. Furthermore, some fatty acids showed p CO2 –reef interactions. In A. millepora, most pigments investigated were reduced at elevated p CO2, while other parameters (e.g. tissue biomass, total proteins, total lipids, protein carbonyls, some fatty acids and pigments) differed between reefs or showed p CO2 –reef interactions. Tissue biomass, total lipids, and cell-protective capacities were distinctly higher in Porites spp. than in A. millepora, indicating higher resistance to environmental stress in massive Porites . However, our data suggest that important biochemical measures remain relatively unaffected in these two coral species in response to elevated p CO2 up to 800 µatm, with most responses being smaller than differences between species and locations, and also when compared with responses to other environmental stressors such as ocean warming.